UPAYA PERBAIKAN KUALITAS UNIT PELAYANAN TEKNIK DENGAN PENDEKATAN LEAN SERVICE (Studi Kasus : PT. PLN APJ Surabaya Selatan) - Mairina Anggarini Francesca (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Technique Service Unit as party who handling directly distribution disturbance, where this unit have big influence on network service quality. Found that compliance on disturbance at present indicating there is waste in network service process then at this research will be quality repair effort from technique service unit from efficiency aspect. In this research method are Data Envelopment Analysis to determining where unit would be primary focus in this research based on efficiency level, Lean Service to improving poor technique service quality, as well as Value Management and dynamic system modeling with software Vensim used for improvement doing. Result of the research indicating whenever Data Envelopment Analysis, Network Service Unit (UPJ) Dukuh Kupang stated inefficiency with Technical Efficiency around 0,73. And repair effort in waste reducing found that waste defect as main cause with seven typesdisturbance causes as Critical to Quality. From CTQ found waste cause as well as repair priority, and repair alternative based on highest RPN value from FMEA then simulated to get best alternative. From available alternative, could be proved that repair recommendation had changed Network Service Unit (UPJ) be efficient with scale efficiency value change from 0,972 to 1. The advantage of this research are problem discussed completely and detail, where repair objectives done on unit really experienced problem. Then causes of the exist problem seek the cause root then priority of repair could precisely. And effort in choosing best alternatives previous simulated with the aim could be known system behavior over the impact of repair that be conducted. Then finally enable a comparison between before systemcondition and after repair